The Possibility of Using Winter Oilseed Rape (Brassica napus L. var. Napus) for Energy Purposes - Siemek, Jakub; Macuda, Jan; Łukańko, Łukasz; Nowak, Jakub; Zając, Tadeusz (Problemy Ekorozwoju, 2020)
Biomass is an important element in the energy balance in the world and plays a large role in efforts to reduce greenhouse gas emissions, and by this is a sustainable source of energy. One method of using biomass is through co-firing with hard coal and lignite in order to generate electricity. An important factor promoting the use of biomass in European Union countries is the fact that CO2 emissions from combustion are not included in the sum of emissions from fuel combustion, in accordance with the principles established in the emission trading system EU ETS. The aim of our research was to examine the possibility of using winter oilseed rape for energy purposes, grown in three research centres located in southern Poland. Two varieties of winter oilseed rape, Adam and Poznaniak, were used during laboratory tests. Analyses were carried out for siliques, seeds, and the main and lateral stem. As part of the study, the calorific value and heat of combustion were determined for 20 samples of winter oilseed rape. The highest values were obtained for seeds, while the lowest were obtained for stems. The calculated values of carbon dioxide emissions factor for the analysed samples were in most cases above 100 kg/GJ and were much higher than the emission during hard coal combustion. In addition, as part of the study, the biomass moisture, amount of ash generated in the combustion process, and the content of volatile compounds as well as carbon and sulphur were determined.